Effect of match location, team ranking, match status and tactical dimensions on the offensive performance in Spanish `La Liga` soccer matches - Gonzalez-Rodenas, J.; Aranda-Malavés, R.; Tudela-Desantes, A.; Calabuig Moreno, F.; Casal, C. A.; Aranda, R. (Frontiers in Psychology, 2019)
The aim of this paper was to study the combined effects of tactical and contextual dimensions on achieving offensive performance in open play possessions from Spanish "La Liga" soccer matches. 1860 team possessions from 20 random matches were evaluated by means of multidimensional observation. Multilevel regression models were constructed to predict the probability to achieve offensive performance according to the tactical and contextual dimensions registered in each possession. Performing penetrative actions after recovering the ball (OR = 1.497; 95% CI: 1.022-2.192; P < 0.05), and progressing by fast attacks (OR = 3.588; 95% CI: 2.045-6.294; p < 0.001) or counterattacks (OR = 7.097; 95% CI: 3.530-14.269; P < 0.001) was more effective to create scoring opportunities than performing a non-penetrative action and progressing by combinative attack, respectively. Also, progressing by long possessions (OR = 5.057; 95% CI: 2.406-10.627; p < 0.001) was more effective than progressing by short possessions to create scoring opportunities. As for contextual dimensions, multivariate analyses showed how playing at home and against high-ranked opponents registered more likelihood of achieving offensive penetration, although no associations were found in the production of scoring opportunities. Tactical dimensions as initial penetration, type of attack and possession length played an important role on achieving offensive penetration and goal scoring opportunities in Spanish Soccer "La Liga".